Impact of Lava-Jato Operation on the financial performance of brazilian companies: an event study - Maria Miguel Peixe, Adriana; Bach, Tatiana Marceda; Vieira da Silva, Wesley; Maia Del Corso, Jansen (Ciências Sociais Aplicadas em Revista, 2023)
This article aims to analyze the impact of Operation Lava-Jato, promoted by the Federal Police of Brazil, on the financial performance of companies listed on the São Paulo Stock Exchange (B3) from 2014 to 2017. This operation revealed the greatest scandal of political corruption in the country, with large amounts of public money transferred to cartels, politicians, and large Brazilian corporations in corruption schemes over the years. Data were collected from 106 Brazilian publicly traded companies related to ten different economic sectors. Documentary research was conducted on financial reports, and information was extracted from 11 different financial variables on the Bloomberg platform. The variable that measured the impact of Lava-Jato Operation was selected considering the increase in the volume of financial information disclosed, and the performance was evaluated by the variable stock price return. Data were analyzed by regression with panel data. The variables that affected financial performance were: multiplicative dummy of the first period, stock price, company size, risk, composition of permanent assets/indebtedness, and permanent assets. This article contributes to understanding the financial context of Brazilian companies, in the face of political and economic instability and corruption. Fluctuations in stock prices in the period studied, given the news released about corruption in Brazil, become a warning for companies to understand the importance of disclosing their financial information to obtain company credibility. Thus, facing the financial market, companies could protect themselves by presenting an emphasis based on financial efficiency, transparency, productivity and the professionalization of their practices.